Forging a Common Vision for Maine’s North Woods - Lilieholm, Robert (Maine Policy Review, 2007)
Robert Lilieholm takes stock of the challenges and opportunities facing Maine’s North Woods, the largest undeveloped forested block in the eastern United States. In the face of changing ownership patterns and development pressures, there is lively debate over current land use policies and trends. Lilieholm suggests that a broader, regional vision for the North Woods might better serve the long-term interests of both the area’s forests and its struggling communities.
Keywords: Maine North Woods; forests; Pinelands National Reserve